Factores de la comunicación en parejas heterosexuales entre 25 a 40 años en convivencia mínima de 3 años (2023)
The focus of the current research is to identify the communication factors of heterosexual couples between 25-40 years old who have been living together for at least 3 years. Keeping in mind that there are different ways to communicate when coexisting with a significant other. In which, there are situations that can lead to find tools to support, prompt and encourage good communication